Síntesis del Sistema Nanoestructurado de Ag-Cu con Propiedades Microbicidas - Ramirez Fosca, Cristian Camilo (Universidad Antonio Nariño, 2023)
The growing occurrence of infections caused by multidrug-resistant pathogens is one of the most relevant health problems worldwide, as it has set off alarms and generated interest in the understanding, detection, and prevention of Antimicrobial Resistance (AMR) worldwide in the search for the development of adequate hygiene and prevention measures, as well as the production of new antimicrobial agents with greater efficiency and their proper use.